1997
DOI: 10.7326/0003-4819-126-8-199704150-00005
|View full text |Cite
|
Sign up to set email alerts
|

Risk for Clinical Thromboembolism Associated with Conversion to Sinus Rhythm in Patients with Atrial Fibrillation Lasting Less Than 48 Hours

Abstract: Among patients presenting with atrial fibrillation that was clinically estimated to have lasted less than 48 hours, the likelihood of cardioversion-related clinical thromboembolism is low. These data support the current recommendation for early cardioversion in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
12

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(82 citation statements)
references
References 0 publications
1
69
0
12
Order By: Relevance
“…The only predictor of increased probability of spontaneous cardioversion was atrial fibrillation duration of <24 hours; 21 similar results were reported by Tejan-Sie and colleagues. 22 These findings have left uncertainty as to the time frame when ED cardioversion is appropriate, the optimal technique of cardioversion, and the best risk stratification tool to apply in determining treatment approach It is critical to point out that the above reports [20][21][22] and the Atrial Fibrillation Follow-up Investigation of Rhythm Management (AFFIRM) trial 23 describe patients Values are %, mean (±SD), or n (%, 95% CI) DCCV = direct current cardioversion; dBP = diastolic blood pressure; HR = heart rate; sBP = systolic blood pressure. *Complications at index visit were defined as emesis, nausea requiring antiemetic medications allergic reaction requiring medications, respiratory distress requiring intervention (bag-valve mask, oral airway, noninvasive positive pressure ventilation, intubation), hypotension requiring intravenous fluids or vasoactive agents within 1 hour of initiation of procedural sedation, new bradycardia requiring pharmacologic intervention or pacing within 1 hour of initiation of procedural sedation, unplanned admission, death, or confirmed thromboembolic event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only predictor of increased probability of spontaneous cardioversion was atrial fibrillation duration of <24 hours; 21 similar results were reported by Tejan-Sie and colleagues. 22 These findings have left uncertainty as to the time frame when ED cardioversion is appropriate, the optimal technique of cardioversion, and the best risk stratification tool to apply in determining treatment approach It is critical to point out that the above reports [20][21][22] and the Atrial Fibrillation Follow-up Investigation of Rhythm Management (AFFIRM) trial 23 describe patients Values are %, mean (±SD), or n (%, 95% CI) DCCV = direct current cardioversion; dBP = diastolic blood pressure; HR = heart rate; sBP = systolic blood pressure. *Complications at index visit were defined as emesis, nausea requiring antiemetic medications allergic reaction requiring medications, respiratory distress requiring intervention (bag-valve mask, oral airway, noninvasive positive pressure ventilation, intubation), hypotension requiring intravenous fluids or vasoactive agents within 1 hour of initiation of procedural sedation, new bradycardia requiring pharmacologic intervention or pacing within 1 hour of initiation of procedural sedation, unplanned admission, death, or confirmed thromboembolic event.…”
Section: Discussionmentioning
confidence: 99%
“…Of these 96 events, only three occurred in patients with duration of atrial fibrillation less than 48 hours. Weigner and coworkers 20 described only three embolic events in a cohort of 375 patients admitted to a cardiology unit for atrial fibrillation. In this group, 250 patients (66.7%) also had spontaneous conversion to sinus rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…12 It was known that cardioversion of patients with AF of >48 hours duration had a 5-7% risk of stroke without preceding anticoagulation. 12 However, it was also known that 14% of patients with AF of <72 hours duration would have atrial thrombi detectable on transoesophageal echo (TOE). 13 Weigner et al prospectively examined 375 patients admitted with symptomatic AF lasting <48 hours in order to determine the incidence of cardioversion-related clinical thromboembolism.…”
Section: Risk Of Thromboembolism Following Cardioversionwhere Does Thmentioning
confidence: 99%
“…This practice was scrutinised by Weigner et al in 1997. 12 It was known that cardioversion of patients with AF of >48 hours duration had a 5-7% risk of stroke without preceding anticoagulation. 12 However, it was also known that 14% of patients with AF of <72 hours duration would have atrial thrombi detectable on transoesophageal echo (TOE).…”
Section: Risk Of Thromboembolism Following Cardioversionwhere Does Thmentioning
confidence: 99%
“…There is therefore inconsistency in the current AF guidelines, where the decisions to initiate and continue anticoagulation are independent of AF burden, but thromboembolic risk in the pericardioversion period is thought to remain relatively low for the first 48 hours. 7 This "48-hour rule," where it is acceptable to perform a cardioversion without first excluding a left atrial thrombus via transesophageal echocardiogram in the first 48 hours, however, is based on a relatively small, nonrandomized study, 23 and no randomized controlled trial data exist to definitively support 48 hours as being a "safe" cutoff time period for thrombus formation. In fact, more recent data obtained from patients with pacemakers and ICDs that have the ability to precisely detect short, subclinical, and asymptomatic AF episodes have demonstrated that the risk of thromboembolism in AF begins to increase much earlier than at 48 hours after AF onset (see below).…”
Section: Atrial Fibrillation Burden and Thromboembolic Riskmentioning
confidence: 99%